2021
DOI: 10.1177/00368504211050293
|View full text |Cite
|
Sign up to set email alerts
|

Research on cutting performance and fatigue life of conical pick in cutting rock process

Abstract: The conical pick is the most crucial tool of roadheader for breaking rock, establishing the conical pick cutting rock and conical pick fatigue life numerical simulation models to investigate the influence of cutting parameters on rock damage, average peak cutting force, specific cutting energy and the conical pick fatigue life. The research results indicate that the width and depth of rock damage increase with increasing cutting depth and cutting speed. The average peak cutting force and the specific cutting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Fatigue damage to picks and, in particular, fatigue breakage of the shanks is a fairly frequent reason for the elimination of picks from the operation, which is strongly dependent on the conditions of use of tangential-rotating picks, including fluctuations in their load from cutting 12 , 21 , 27 , 36 , 37 . Shank fatigue fractures are particularly critical.…”
Section: Construction and Technological Modifications Of Tangential-r...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue damage to picks and, in particular, fatigue breakage of the shanks is a fairly frequent reason for the elimination of picks from the operation, which is strongly dependent on the conditions of use of tangential-rotating picks, including fluctuations in their load from cutting 12 , 21 , 27 , 36 , 37 . Shank fatigue fractures are particularly critical.…”
Section: Construction and Technological Modifications Of Tangential-r...mentioning
confidence: 99%
“…These studies use modern research techniques, including the finite element method (FEM) and the discrete element method (DEM), as well as measurements at laboratory stations and in operational conditions. Theoretical and experimental research mainly concerns: the mechanics of rock cutting with conical picks 5 , the prediction of the load on conical picks and the energy consumption of mining, especially hard rocks 6 9 , the formation of stresses in the pick tip and its shaft 10 12 , the interaction of the pick with the pick holder 13 , the distribution of stresses in the pick holder with a pick placed within it 14 , and the wear mechanisms of the picks in the rock mining process 15 . …”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [14] simulated the rock cutting process with different cutting parameters and structural parameters of the tool, and the results showed that the cutting force and the number of accumulated cracks increased with increasing cutting speed, cutting depth, tool tip angle, and wear of the picks. Zeng et al [15] established a simulation model for cutting rock and fatigue life of picks to study the influence of cutting parameters on rock damage and mean cutting peak force. It was found that the mean cutting peak force increased with the increasing cutting depth and cutting speed.…”
Section: State Of the Artmentioning
confidence: 99%
“…Jiang et al 13 studied the different water jet of cutting head influence on specific cutting energy, compared impact of the water jet on rock breaking performance and determined the best parameters of the water jet assisted rock breaking to improve the rock breaking efficiency. Zeng et al 14 studied the cutting force and rock damage with different cutting parameters and investigated the rock breaking performance and fatigue life of conical pick in the process of conical pick cutting rock 15 .…”
Section: Introductionmentioning
confidence: 99%